RESPON PEMBERIAN PUPUK HAYATI TERHADAP SIFAT BIOLOGI TANAH PADA TANAMAN KEDELAI DI ULTISOLS - Andriani, Evi; Bertham, Yudhi Harini (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2016)
The purposes of this research are (1) to know the influence of genotype and biological fertilizer to the soil biological properties, and (2) to know the influence of genotype and biological fertilizer to the soybean plants productivity at its ultisols. This experiment was conducted at experimental garden of Bengkulu University. It was arranged in factorial split plot design and consisted of two factor. The first factor was soybean cultivars i.e. Pangrango, Ceneng, and DS1 (Malabar and Kipas Putih variety breeding). The second factor was double inoculation of Rhizobium and VAM i.e. Glomus manihotis + Rhizobium of KLR 5.3 strain, Glomus manihotis + Rhizobium of TER 2.2 strain, Gigaspora margarita + Rhizobium of KLR 5.3 strain, Gigaspora margarita + Rhizobium of TER 2.2 strain, fertilizer NPK at recommended dosage without inoculants respectively. The collected data was analyzed statistically and tested by F test at level of 5% and continued with Duncan Multiple Range test for differences among the treatments. The result of the research showed that (1) the soil that had been planted genotype DS1 soybean has the highest level of C-Organic (2,69%) compare with pangrango or ceneng and biological fertilizer produces higher level of respiration than its control. (2) cenengâs genotype produce the effective amount of nodules, plant dry weight (3,90 g), and seed weight (5,66 g) is higher than if we compare with pangrango and DSI.Keywords : soybean, biofertilizer technology , Ultisols